2016
DOI: 10.1038/mp.2016.18
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide significant risk factors for Alzheimer’s disease: role in progression to dementia due to Alzheimer's disease among subjects with mild cognitive impairment

Abstract: Few data are available concerning the role of risk markers for Alzheimer's disease (AD) in progression to AD dementia among subjects with mild cognitive impairment (MCI). We therefore investigated the role of well-known AD-associated single-nucleotide polymorphism (SNP) in the progression from MCI to AD dementia. Four independent MCI data sets were included in the analysis: (a) the German study on Aging, Cognition and Dementia in primary care patients (n=853); (b) the German Dementia Competence Network (n=812)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 48 publications
3
68
0
Order By: Relevance
“…To date, except for CLU and APOE, few of the identified genetic risk variants in case-control GWAS for AD have shown a consistent effect on disease progression in MCI patients [42]. Our study now adds to this list PLCG2 as a strong protector of cognitive function at the MCI stage.…”
Section: Discussionmentioning
confidence: 64%
“…To date, except for CLU and APOE, few of the identified genetic risk variants in case-control GWAS for AD have shown a consistent effect on disease progression in MCI patients [42]. Our study now adds to this list PLCG2 as a strong protector of cognitive function at the MCI stage.…”
Section: Discussionmentioning
confidence: 64%
“…AD genetic risk scores have been associated with increased risk of late life cognitive impairment [55], AD risk [56], greater risk of conversion from MCI to AD [54,57,58], and discriminating an AD group from controls [59]. Research on genetic risk approaches have used several procedures for calculating risk scores.…”
Section: Introductionmentioning
confidence: 99%
“…Rodriguez-Rodriguez et al compared those in the 1 st and 3 rd tertile of PRS (OR: 1.32, 95% CI: 0.57-3.06). Neither of the hazard models used by Lacour et al and Andrews et al produced significant results (Lacour HR: 1.18, 95% CI: 0.37-2.0; Andrews HR: 1.05, 95% CI: 0.86-1.29) [29,37]. However, Andrews et al found their PRS was associated with an increased risk of transitioning from normal cognition to dementia (HR = 4.19, 95% CI: 1.72-10.20) [37].…”
Section: Mild Cognitive Impairment To Ad Conversionmentioning
confidence: 84%
“…The findings for MCI conversion prediction are more mixed. Of the three studies reporting negative results, two had relatively low power [11,29]. Almost all the studies exploring PRS prediction accuracy report that there is some overlap between cases and controls at high polygenic risk.…”
Section: Prs In Disease Predictionmentioning
confidence: 99%
See 1 more Smart Citation